Size Effects in Residual Stress Formation during Quenching of Cylinders Made of Hot-Work Tool Steel - Manuel Schemmel; Petri Prevedel; Ronald Schöngrundner; Werner Ecker; Thomas Antretter (Advances in Materials Science and Engineering)
The present work investigates the residual stress formation and the evolution of phase fractions during the quenching process of cylindrical specimens of different sizes. The cylinders are made of hot-work tool steel grade X36CrMoV5-1. A phase transformation kinetic model in combination with a thermomechanical model is used to describe the quenching process. Two phase transformations are considered for developing a modelling scheme: the austenite-to-martensite transformation and the austenite-to-bainite transformation. The focus lies on the complex austenite-to-bainite transformation which can be observed at low cooling rates. For an appropriate description of the phase transformation behaviour nucleation and growth of bainite are taken into account. The thermomechanical model contains thermophysical data and flow curves for each phase. Transformation induced plasticity (TRIP) is modelled by considering phase dependent Greenwood-Johnson parameters for martensite and bainite, respectively. The influence of component size on residual stress formation is investigated by the finite element package Abaqus. Finally, for one cylinder size the simulation results are validated by X-ray stress measurements.